Critical Study : Independent Curriculum from the Perspective of Educational Philosophical Schools and the Philosophy of Ki Hajar Dewantara - Fitriani, Herdiyana; Suastra, I Wayan; Atmaja, Ananta Wikrama Tungga (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2023)
The Merdeka Curriculum is a development of the K13 curriculum which focuses on aspects of developing the potential, talents, and interests of students through digitizing learning with the use of technology. This curriculum is a starting point for facing the Society 5.0 era which predominantly uses technology. The Merdeka Curriculum is compiled based on four schools of educational philosophy, each of which has characteristics that complement each other in curriculum preparation, only the dominance is different in each curriculum. The development of an independent curriculum needs to be reviewed in terms of educational philosophy so that the dominance of this philosophy can be identified so that the output results are identified with the basis of the curriculum. This research uses a qualitative method with a literature study approach (library research), primary sources are obtained from scientific literature and secondary sources are obtained from supporting sources, such as essays, papers, seminar results, and others. The results of this study are first, the perennialism school of philosophy does not dominate in the independent curriculum because it is only used as a stronghold of cultural values so as not to collapse in the modern era. Second, the essentialism school of philosophy dominates in the content of learning materials. Third, the progressivism school of philosophy fills in the process of student character building through the Pancasila student profile. Fourth, the constructionism school of philosophy dominates the whole because of the renewal of the structure and system of school stakeholders.